2018
DOI: 10.1038/s41591-018-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of resistance to chimeric antigen receptor T cell therapy by transduction of a single leukemic B cell

Abstract: We report a patient relapsing 9 months after CD19-targeted CAR T cell (CTL019) infusion with CD19- leukemia that aberrantly expressed the anti-CD19 CAR. The CAR gene was unintentionally introduced into a single leukemic B cell during T cell manufacturing, and its product bound in cis to the CD19 epitope on the surface of leukemic cells, masking it from recognition by and conferring resistance to CTL019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
381
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 505 publications
(390 citation statements)
references
References 36 publications
6
381
0
3
Order By: Relevance
“…Surprisingly, a recent report uncovered an unexpected resistance mechanism to CD19-CAR-T cell therapy: Ruella et al showed that during the cell production process, a contaminating lymphoma B-cell underwent transduction leading to CD19-CAR expression. Cis interactions with surface CD19 resulted in its shielding by the CAR, making the antigen inaccessible to CAR-T cells [363]. While this phenomenon was not reported elsewhere, it does underscore the need to care for stringent production processes but more importantly, it demonstrates to what extent the development and mechanisms of resistance to engineered lymphocyte treatments may be unusal.…”
Section: Resultsmentioning
confidence: 89%
“…Surprisingly, a recent report uncovered an unexpected resistance mechanism to CD19-CAR-T cell therapy: Ruella et al showed that during the cell production process, a contaminating lymphoma B-cell underwent transduction leading to CD19-CAR expression. Cis interactions with surface CD19 resulted in its shielding by the CAR, making the antigen inaccessible to CAR-T cells [363]. While this phenomenon was not reported elsewhere, it does underscore the need to care for stringent production processes but more importantly, it demonstrates to what extent the development and mechanisms of resistance to engineered lymphocyte treatments may be unusal.…”
Section: Resultsmentioning
confidence: 89%
“…A report of the incidental CAR transduction of B cells, which conferred resistance to subsequent CAR T cell therapy 38 , highlights the importance of having a purified starting product. Strategies to optimize the input apheresis product before CAR T cell manufacturing, generally through T cell selection and enrichment, have been First, CAR T cell failures have several causes: for some patients, the CAR T cell product cannot be successfully manufactured or the generated CAR T cells do not expand sufficiently (either during manufacturing in vitro or after administration in vivo); in other patients, the problem of limited persistence in vivo is a potential mechanism underlying disease relapse.…”
Section: Wwwnaturecom/nrclinoncmentioning
confidence: 99%
“…However, it has been recognized recently they may induce immunoreaction and insertional oncogenesis . Ruella et al . reported that the CAR gene was unintentionally introduced into a single leukemic B cell during T cell manufacture via lentiviral transduction, which caused the patient to relapse 9 months after CD19‐targeted CAR T cell (CTL019) infusion.…”
Section: Introductionmentioning
confidence: 99%